2013
DOI: 10.1088/0031-9155/58/9/2861
|View full text |Cite
|
Sign up to set email alerts
|

A reference dataset for deformable image registration spatial accuracy evaluation using the COPDgene study archive

Abstract: Rationale and Objectives Landmark point-pairs provide a strategy to assess deformable image registration (DIR) accuracy in terms of the spatial registration of the underlying anatomy depicted in medical images. In this study, we propose to augment a publicly available database (www.dir-lab.com) of medical images with large sets of manually identified anatomic feature pairs between breath-hold computed tomography (BH-CT) images for DIR spatial accuracy evaluation. Materials and Methods 10 BH-CT image pairs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 49 publications
(69 reference statements)
0
97
0
Order By: Relevance
“…In contrast to the two previous databases that were acquired with respiratory-correlated 4D reconstruction imaging, the COPDgene study [41] provides 3D breath-hold CT lung images. It consists of 10 cases, each case including a pair of images at end-inhale and end-exhale, together with 300 publicly-available landmarks per image.…”
Section: D Breath-hold Ct Dir Copdgene Databasementioning
confidence: 99%
“…In contrast to the two previous databases that were acquired with respiratory-correlated 4D reconstruction imaging, the COPDgene study [41] provides 3D breath-hold CT lung images. It consists of 10 cases, each case including a pair of images at end-inhale and end-exhale, together with 300 publicly-available landmarks per image.…”
Section: D Breath-hold Ct Dir Copdgene Databasementioning
confidence: 99%
“…In an effort to provide consistent datasets for algorithm validation, several researchers have made their ground‐truth models publicly available. Examples include the extended cardiac–torso (XCAT) phantom, (3) the point‐validated pixel‐based breathing thorax model (POPI model), (4) the DIR‐Lab Thoracic 4D CT model, 5 , 6 and those provided as part of the EMPIRE 10 challenge (7) . In an effort to improve the correlation of computer‐based phantoms with the actual anatomical changes seen over a course of radiation therapy, the current authors previously developed synthetic datasets derived from clinical images of real head and neck patients (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Notice that DM-ALOST gave a higher correlation than the other registration methods, although none of the differences were significant. It showed that DM-ALOST gave best registration results among all six methods [32].…”
Section: Correlation Of Manual To Semi-automatic Measurements Of Relamentioning
confidence: 93%